Carbon storage capacity of different forest tree species and their role in mitigating climate change (Bangladesh Journal of Botany, 2026)
Carbon dioxide is the most important atmospheric component, as it traps heat and creates conditions that are adverse to all living organisms. Only plants can capture CO₂ from the atmosphere and help reduce it through photosynthesis. The determination of carbon sequestration capacity is crucial for assessing the ability of each tree species to mitigate global warming. The research was conducted in an artificially planted forest area to determine biomass and carbon storage capacity. A systematic sampling and non-destructive method were followed to determine the carbon sequestration capacity of five tree species. The present research revealed that carbon storage ranged from 215.62 kg tree-1 to 669.82 kg tree-1 at 25-year-old established orchards. The highest biomass was found in Albizia procera, and the lowest in Lagerstroemia speciosa Statistical analysis revealed that carbon storage varied significantly (p < 0.05) among the five tree species.Bangladesh J. Bot. 55(2): 381-386, 2026 (June)